APPLICATION OF VOICE RECOGNITION - ABU BAKAR, KAMARUL AZMAN (Universiti Teknologi Petronas, 2005)
Voice recognition or speech recognition is the capability of a computer to recognize or respond to spoken words and commands. Speech& Voice recognition enables "hands-free" control of various electronic devices which is a particular help to many disabled persons and the automatic creation of "print-ready" dictation. Among the earliest applications for speech & voice recognition were automated telephone systems and medical dictation software (Transcription). These applications can be enhanced to wider application where persons can control a system by using voice command. Therefore to fill up the gap, this project is basically to create a system that can control the part or the whole house appliances by applying voice command added with some other extra features. The extra features included operating windows application, words translation, and reading notes. The house appliances can be lighting, fan, air-conditioner, garage door and etc. This system operates like a switching system where the main objective is to control the application ON/OFF operation. The main different is this system used voice command as the controller rather than manual switching by hand. There will be graphical interface that helps the user to monitor and control the system. Throughout this report, the author will explain in detail about the project. IV